Book Review of Culture-Infused Counselling (2nd edition) - Paré, David (Canadian Journal of Counselling and Psychotherapy, 2012)
Culture-Infused Counselling is the second edition of Arthur and Collins’s text, originally published in 2005. The book treats culture as ubiquitous, and advocates an approach to counselling that is “culture-infused” in the sense that practitioners never step out of culture to engage in any of their professional activities, including counselling, supervising, teaching, consulting, assessing, and researching. This edition is significantly revised to include new material addressing the complexities of cultural identity and an additional chapter on the role of social justice and advocacy in counselling. Culture-Infused Counselling verges on encyclopedic in scope and is a key and valuable resource with a distinctly Canadian focus.